ANALISIS GAMBARAN TINGKAT KEPARAHAN MALOKLUSI DENTAL REMAJA USIA 15-18 TAHUN DI BANJARMASIN BERDASARKAN INDEKS ICON (INDEX OF COMPLEXITY, OUTCOME, AND NEED) - Erine Febrianti; Diana Wibowo; Sherli Diana; Isnur Hatta; Alexander Sitepu (Dentin, 2024)
ABSTRACTBackground: Malocclusion is a multifactorial problem that occurs due to general and local factors. Teeth crowding is one of the characteristics of malocclusion that often occurs in adolescents. Appearance is important for teenagers to increase self-confidence. Part of the appearance that results from the teeth and mouth is a smile. The need for orthodontic treatment can be measured using the Index of Complexity, Outcome, and Need (ICON) which calculates the complexity, success, and necessity of orthodontic care. Purpose: To find out an overview of the severity of dental malocclusion in adolescents aged 15-18 years in Banjarmasin based on the ICON (Review of high school students in North Banjarmasin and Central Banjarmasin District). Methods: This was a descriptive analytics study with a cross sectional design. Sampling techniques using random sampling in teenagers aged 15-18 years as many as 356 respondents. Malocclusion severity data was obtained through ICON measurement. Results: The results of this study were the highest level of malocclusion complexity in the mild category by 147 respondents, the most aeshthetic component is in category no treatment need (159 respondents), cross-bite is in category 0 (205 respondents, crowding teeth is in category 1 (101 respondents), diastema teeth is in category 3 (18 respondents), open bite is in category 0 (106 respondents), and the antero-posterior tooth relationship is in category 0 (216 respondents). Conclusion: The degree of complexity of dental malocclusion in adolescents 15-18 years old in Banjarmasin were mostly found in the light category.Keyword: Orthodontic, Malocclusion, ICON ABSTRAKLatar Belakang: Maloklusi adalah masalah multifaktorial yang terjadi karena faktor umum dan faktor lokal. Gigi berjejal adalah salah satu karakteristik dari maloklusi yang sering terjadi pada remaja. Penampilan merupakan hal yang penting bagi remaja untuk meningkatkan kepercayaan diri. Bagian dari penampilan yang dihasilkan dari gigi dan mulut adalah senyum. Kebutuhan akan perawatan orthodonti dapat diukur menggunakan Index of Complexity, Outcome, and Need (ICON) yang memperhitungankan kompleksitas, keberhasilan, dan kebutuhan dari perawatan orthodonti. Tujuan: Untuk mengetahui gambaran tingkat keparahan maloklusi dental remaja usia 15-18 tahun di Banjarmasin berdasarkan indeks ICON (Tinjauan pada pelajar SLTA di Banjarmasin Utara dan Banjarmasin Tengah). Metode: Penelitian ini menggunakan metode deskriftik analitik dengan desain cross sectional. Teknik pengambilan sampel menggunakan random sampling pada remaja usia 15-18 tahun sebanyak 356 responden. Data tingkat keparahan maloklusi diperoleh melalui pengukuran indeks ICON. Hasil: Hasil penelitian ini yaitu tingkat kompleksitas maloklusi terbanyak ada pada kategori ringan yaitu 147 responden, aeshthetic component paling banyak ada pada kategori tidak membutuhkan perawatan (159 responden), gigitan silang atau crossbite ada pada kategori 0 (205 responden), gigi berdesakan atau crowding ada pada kategori 1 (101 responden), gigi berjarak atau diastem ada pada kategori 3 (18 responden), over bite ada pada kategori 0 (103 responden), oven bite ada pada kategori 3 dan 4 (12 responden), dan relasi gigi antero-posterior ada pada kategori 0 (216 responden). Kesimpulan: Tingkat kompleksitas maloklusi dental pada remaja usia 15-18 tahun di Banjarmasin banyak ditemukan pada kategori ringan.Kata kunci: ICON, Maloklusi, Orthodontik